2003
DOI: 10.1097/00004770-200303000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A New Solution for the Removal of the Smear Layer

Abstract: Various organic acids, ultrasonic instruments, and lasers have been used to remove the smear layer from the surface of instrumented root canals. The purpose of this study was to investigate the effect of a mixture of a tetracycline isomer, an acid, and a detergent (MTAD) as a final rinse on the surface of instrumented root canals. Forty-eight extracted maxillary and mandibular single-rooted human teeth were prepared by using a combination of passive step-back and rotary 0.04 taper nickel-titanium files. Steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
477
3
57

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(566 citation statements)
references
References 13 publications
29
477
3
57
Order By: Relevance
“…Photomicrographs were taken at 2000× magnification. One blinded and calibrated observer (kappa=0.88) classified erosion in each image according to the following criteria, adapted from Torabinejad et al 14 score 0 = smear layer covering almost all dentin surface, with few or no opened tubules; score 1 = no erosion: all tubules looked normal in appearance and size; score 2 = moderate erosion: the peritubular dentin was eroded; score 3 = severe erosion: the intertubular dentin was destroyed and the tubules were connected to each other. The area to be analyzed was selected randomly, with a lower magnification (200×).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photomicrographs were taken at 2000× magnification. One blinded and calibrated observer (kappa=0.88) classified erosion in each image according to the following criteria, adapted from Torabinejad et al 14 score 0 = smear layer covering almost all dentin surface, with few or no opened tubules; score 1 = no erosion: all tubules looked normal in appearance and size; score 2 = moderate erosion: the peritubular dentin was eroded; score 3 = severe erosion: the intertubular dentin was destroyed and the tubules were connected to each other. The area to be analyzed was selected randomly, with a lower magnification (200×).…”
Section: Methodsmentioning
confidence: 99%
“…6,11 However, it is known that such chemical auxiliary substances are responsible for reaching the inorganic structure of dentin and thereby cause changes in dentin microhardness 8,12,13 and erosion. 12,14,15,16 Some studies have suggested that these changes could increase the susceptibility to tooth fracture. 17 A solution known as QMiX has been suggested in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of CHX with an added surfactant and EDTA is used to increase penetration to the dentinal tubules (4,49).…”
Section: Chlorhexidine (Chx)mentioning
confidence: 99%
“…This mixture acts as a chelator and has antimicrobial activity. As it has no organic tissue-dissolving effect, its use after NaOCl at the end of chemomechanical preparation is recommended (49).…”
Section: Mixture Of Tetracycline Isomer Acid and Detergent (Mtad)mentioning
confidence: 99%
See 1 more Smart Citation